KONTROVERSI PEMIKIRAN IGNAZ GOLDZIHER DAN IMPLIKASINYA PADA TREN STUDI ISLAM ABAD 19-21 M - Mauizah, Adzkiya Zayyan; Hidayat, Fahri (FiTUA: Jurnal Studi Islam, 2024)
The purpose of this research is to explore the controversy of Ignaz Goldziher's thought and its implications for the trend of Islamic studies in the West (19-21 AD). This research is a type of library research with a focus on character studies using historical research methods. The results and discussion in this study found five thoughts of Ignaz Goldziher in Islamic studies, namely: Ignaz Goldziher’s scepticism towards the Qur’an; Ignaz Goldziher’s classification of mufassir; differentiation of the meaning of hadith and sunnah according to Ignaz Goldziher; Ignaz Goldziher’s scepticism towards hadith; and Ignaz Goldziher’s views regarding Islamic sharia law. Then, for the controversy of the implications of Ignaz Goldziher's thoughts on the development of Islamic studies trends in the 19th-21st centuries AD is the emergence of groups of supporters and opponents of his thoughts. In addition, it was also found that the implications of his thoughts not only triggered the emergence of those who supported and opposed his opinions, but also had an impact on strengthening indirectly the line of thought of the Jaringan Islam Liberal (JIL, Islamic Liberal Networks) in Indonesia.